Effect of chemoradiation on the size of the thyroid gland. Issue 4 (1st October 2020) - Rivas, Ana Marcella; Larumbe-Zabala, Eneko; Diaz-Trastoy, Olaia; Schurr, Ryan Nicholas; Jones, Catherine; Abdulrahman, Ramzi; Dar, Nabeel; Lado-Abeal, Joaquin
Abstract: We aimed to evaluate changes in thyroid gland size during the treatment of malignancies outside the head and neck with chemotherapy and/or external beam radiation. We performed a retrospective review of records of adult patients treated at our institution with external beam radiation to the chest and/or chemotherapy with taxanes, alkylating agents, and/or a topoisomerase II inhibitor. Neck and chest computed tomography (CT) images were used to calculate thyroid gland volume before and after therapy, using Vitrea ® software or the volumetric ellipsoid method. Thirty-seven patients were included. After treatment, there was a significant reduction in thyroid gland volume of 14.0% ( P < 0.01) using Vitrea and 17.1% ( P < 0.05) using the volumetric ellipsoid method. Exposure to radiation or chemotherapy was not found to be associated with the degree of thyroid gland reduction, nor was the number of days between CT scans or the stage of the malignancy being treated. Finally, the degree of thyroid gland size reduction did not predict mortality. Our results showed that the treatment of malignancies outside the head and neck with chemotherapy and/or external beam radiation results in a reduction in thyroid gland size. The impact on thyroid gland function remains unknown.